Mailbox 16 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
MailboxMany sharp-eyed readers have pointed out to us that in the photo next to the article about yams in Ghana (Spore 87, June 2000, page 8), the woman had put all her cassava in one basket, and not the yams she planned to use. Point taken....